Women Make the Difference in Heart Disease - Angela H.E.M. Maas; Harry Suryapranata (The Indonesian Heart Association, 2007)
Cardiovascular disease develops 10 to15 years later in women than in men and is the major cause of death in women older than 65 years of age. The risk of heart disease in women however is still underestimated and many women are not aware of their own risk factors.In a recent report from the European Heart Survey on stable angina pectoris it was found that women are less likely to be referred for functional testing for ischemia, with a lower rate of diagnostic angiograms and interventional procedures.The under-recognition of heart disease and differences in clinical presentation in women lead to less aggressive treatment strategies and a lower representation of women in clinical trials. In the current review we summarize the major issues that are important in the diagnosis and treatment of coronary heart disease (CHD) in women.